2013
DOI: 10.1590/s1981-38212013000200002
|View full text |Cite
|
Sign up to set email alerts
|

New policies for science and technology and the impacts on public research institutes: a case study in Brazil

Abstract: This article aims to discuss how technological production has been affected by new organizational patterns of funding and evaluation, international transformations in terms of the reorganization of research centers, and changes in innovation practices. Researchers and scientists have had their activities redefined through new organizational formats that today are well-established. The purpose here is to verify the impacts that these tendencies have had on the scientific and technological production of Public R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…(3) e degree of government support. Cao and Li [38], Andrade et al [39] found that policy support has a significant impact on the innovation efficiency. is paper chooses the proportion of government investment in per capita public education expenditure and R&D expenditure as the indicator of government support.…”
Section: Analysis Of the Impact On The Efficiency Of Scientific And Technological Innovation In Universities 431 Selection Of Indicators mentioning
confidence: 99%
“…(3) e degree of government support. Cao and Li [38], Andrade et al [39] found that policy support has a significant impact on the innovation efficiency. is paper chooses the proportion of government investment in per capita public education expenditure and R&D expenditure as the indicator of government support.…”
Section: Analysis Of the Impact On The Efficiency Of Scientific And Technological Innovation In Universities 431 Selection Of Indicators mentioning
confidence: 99%